Efektivitas Penerapan Pasal 107 Ayat (2) Undang-Undang Nomor 22 Tahun 2009 tentang LLAJ Dalam Menekan Angka Kecelakaan di Kota Banjarmasin - Muhammad Hafiidh; Nurul Listiyani (Jurnal Penegakan Hukum Indonesia, 2022)
The objectives to be achieved in this research are to find out how the regulation regarding the level of compliance with turning on the motorcycle headlights during the day and how the effectiveness of the motorcycle headlights obligation during the day reduces the number of motorcycle accidents. The research method used is an empirical legal research method which is also called field research by interviewing informants and knowing respondents' perceptions which are then compared to draw conclusions. The results of the study show that the regulation regarding compliance with turning on the motorcycle headlights and how the effectiveness of the motorcycle's headlight obligation during the day reduces the number of motorcycle accidents. Based on the results of research conducted by researchers, it can be concluded that, in Law Number 22 of 2009 concerning Road Traffic and Transport Article 107 paragraph (2) regarding compliance with turning on the main lights during the day for two-wheeled drivers to reduce the number of accidents in the jurisdiction of the City Police. Banjarmasin is not effective even though the number of violations of compliance with turning on the main lights during the day for two-wheelers is decreasing.